Kontroversi Penerapan Presidential Threshold Dalam Pemilihan Presiden - Azzahra Maya Rizki, Azzahra Maya Rizki (Universitas Nahdlatul Ulama Blitar, 2022)
This article aims to examine article 222 of law number 7 of 2017 concerning general elections which limits the right to vote for citizens to become president / vice president with a presidential threshold of 20% ( twenty percent ) of the number of seats in the DPR or obtan 25% (twenty five percent ) of the nationally valid votes in the previous election for members of the DPR were reviewed from the point of view of democratic theory.